The learner of PLAc in a refuge situation: what the “voice” of teaching reveals - Lôpo Ramos, Ana Adelina; Oliveira das Neves, Aline Cristina (Universidade Estadual Paulista, 2021)
The learner of Portuguese as a Welcoming Language (PLAc) has been an increasingly frequent reality in Brazilian public schools. This paper presents an analysis of the teaching “voice” of two teacher-collaborators about the pedagogical challenge of serving this target audience. The theoretical and methodological approach is based on Critical Discourse Analysis (ADC), based on the contributions of Fairclough (2001), observing aspects of their representation as professionals, the representation they have of their students, and how they perceive Brazil as a welcoming country. In addition, the studies of Barbisan and Megid (2018) and of Clandinin and Rosiek (2007), on narratives are the pillars of this work. Language of Reception (LAc) is briefly commented on, in light of Ançã (2008; 2013), Audras et al. (2020), Barbosa and São Bernardo (2017), among others. The results reveal representations that demand modus operandi peculiar to a public in need of reception.